1992
DOI: 10.1111/j.1365-246x.1992.tb04645.x
|View full text |Cite
|
Sign up to set email alerts
|

A study of rocket measurements of ionospheric currents-IV. Ionospheric currents in the transition zone and the overview of the study

Abstract: The study of rocket measurements suggests the following conclusions. (i) Ionospheric currents are basically in two layers. (ii) The upper current layer with a steady altitude extent of 18 f 3 km is global and should be regarded as the worldwide part of the Sq current system. (iii) The intense eastward lower current layer at the magnetic dip equator that terminates in a focus within 2" to 4" dip latitude, together with the reverse westward lower current layer that peaks around 5.3 f 0.7" dip latitude, should be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Furthermore, since our analysis used daily values, the weak correlation also implies that day-to-day variability in Sq and EEJ is largely uncorrelated. In addition, some studies have suggested that the EEJ has its own circuit whose return paths and intensity variations are different from the global Sq current (Ogbuehi et al 1967;Onwumechili, 1992b). This could further contribute to the weak correlation observed at the dip equator.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, since our analysis used daily values, the weak correlation also implies that day-to-day variability in Sq and EEJ is largely uncorrelated. In addition, some studies have suggested that the EEJ has its own circuit whose return paths and intensity variations are different from the global Sq current (Ogbuehi et al 1967;Onwumechili, 1992b). This could further contribute to the weak correlation observed at the dip equator.…”
Section: Discussionmentioning
confidence: 99%
“…Rocket measurements by Onwumechili (1992b) showed that the EEJ and Sq at the dip equator flow at different altitudes where the effective conductivities, electric fields, and winds are different. This suggests that Sq and EEJ are driven by different factors, which could naturally result in a weak correlation between the two.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations